Assimilation of dietary phytosterols by Pacific oyster (Crassostrea gigas) spat - Knauer, J; Barrett, S M; Volkman, J K; Southgate, Paul C (Aquaculture Nutrition, 1999)
Pacific oyster Crassostrea gigas spat were fed either the microalga Chaetoceros muelleri, Isochrysis aff. galbana (strain T-IS0) or Pavlova lutheri to investigate the effect of dietary phytosterols on the sterol composition of spat tissues. After a 6-week feeding period the sterol profile of spat tissues generally reflected that of the diet, but not all sterols were assimilated with the same efficiency. 4-Desmethyl sterols, such as cholesterol and 24-methylcholesterol, were readily incorporated into spat tissues but 4-methyl sterols, such as 4-methyl-24-ethyl-5α-cholest-22E-en-3β-ol and the unusual 3,4-dihydroxy 4-methyl sterol 24-methylpavlovol present in P. lutheri, were poorly assimilated by spat. The absolute content of every sterol decreased in spat that had been starved for 6 weeks, but the relative sterol composition was similar to the initial sterol profile. However, the relative level of cholesterol increased, indicating the important role of this sterol in spat metabolism.